Cybersecurity Planning Insight: CSCD (Cyber Security and Cyber Defense) Control: Framework For Strategic Direction and Governance - Hasan, Mahmudul (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management